Glutathione S-transferase M1, T1, and P1 polymorphisms and periodontitis in a Caucasian population: a case-control study - Pavla Izakovicova; Antonin Fassmann; Ladislav Dusek; Lydie Izakovicova Holla (BMC, 2024)
Abstract Background Glutathione S-transferases (GSTs) play important roles in protecting cells against oxidative stress and toxic chemicals. This study aimed to investigate the distribution of GSTM1, GSTT1, and GSTP1 variants and their roles in periodontitis susceptibility in a Caucasian population. Methods We analyzed 406 participants, including 204 healthy controls and 203 periodontitis patients. A multiplex polymerase chain reaction (PCR) approach was used to analyze GSTM1 and GSTT1 loci. GSTP1 variants were detected by PCR-haplotyping method in a subgroup of participants (N = 350). Chi-square or Fisher´s exact tests were used to compare genotypic and allelic differences. The Bonferroni method was applied to correct for multiple comparisons (pcorr). Results The GSTM1 genotype distribution did not differ significantly between controls and periodontitis patients (p = 0.44). Additionally, the wild/null genotypes of GSTT1, Ile105Val and Ala114Val frequencies of GSTP1 were not significantly different between the two groups after correction for multiple comparisons (p = 0.05, p = 0.55, p = 0.02, pcorr>0.05, respectively). The GSTM1 and GSTP1 Ile105Val gene variants were similarly distributed between non-smokers and smokers in both groups (p = 0.38, p = 0.20, and p = 0.14, p = 0.35, respectively). However, the wild genotype of the GSTT1 and Ala114Ala variant of the GSTP1 genes were present more frequently in non-smoking periodontitis patients than in non-smoking controls (p = 0.03, pcorr>0.05, and p = 0.009, pcorr>0.05, respectively) although their frequencies did not differ between smoking periodontitis patients and smoking controls (p = 0.23, p = 0.68, respectively). Conclusions This study in a Czech Caucasian population did not confirm a highly significant association between GST gene variants and susceptibility to periodontitis, as previously reported by Arshad and colleagues in Pakistanis. However, a weak relationship between GSTT1 and GSTP1 rs1138272 polymorphisms and periodontitis in non-smokers was observed.